What works to reduce inequalities in higher education? A systematic review of the (quasi-)experimental literature on outreach and financial aid. (February 2020) - Herbaut, Estelle; Geven, Koen
Abstract: The quickly growth of the (quasi-)experimental literature on policy interventions in higher education provides an opportunity to identify the causal effects of these interventions on disadvantaged students. We selected 71 studies and rigorously gathered and compared more than 200 causal effects of outreach and financial aid interventions on access and completion rates of disadvantaged students in higher education. We find that outreach policies are broadly effective in raising access of disadvantaged students when they include active counselling or simplify the university application process, but not when they only provide general information on higher education. In terms of financial aid, we find that need-based grants do not systematically raise enrolment rates but only lead to improvements when they provide enough money to cover unmet need and/or include an early commitment during high school. Still, need-based grants quite consistently appear to improve completion rates of disadvantaged students. In contrast, the evidence indicate that merit-based grants only rarely improve outcomes of disadvantaged students. Finally, interventions combining outreach and financial aid have brought promising results although more research on these mixed-interventions is still needed. We also discuss the theoretical implications of these findings for our understanding of the mechanisms driving social inequalities in higher education.